Experimental analysis of the effect of static yaw error on wind turbine nacelle anemometer measurements - Astolfi, Davide; Gao, Linyue; Pandit, Ravi; Hong, Jiarong (Institute of Electrical and Electronics Engineers (IEEE), 2023)
The operation of wind turbines in real-world environments can be affected by the presence of systematic errors, which might diminish the Annual Energy Production up to 3-4%. Therefore, it is fundamental to leverage the availability of SCADA-collected measurements in order to formulate reliable diagnosis methods. The static yaw error of a wind turbine occurs when, due to wind vane or installation defects, the rotor plane is systematically not perpendicular to the wind flow. The present work is devoted to the experimental analysis of how the presence of a static yaw error affects the wind turbine nacelle anemometer measurements. Measurements collected at the Eolos Wind Research Station at the University of Minnesota are analyzed. The qualifying aspect is that a utility-scale wind turbine has been fully controlled and imposed to set to a non-vanishing yaw error. Furthermore, approximately two rotor diameters south of the turbine there is a meteorological tower which provides unbiased measurements of the environmental conditions. The main result of this work is that, for given wind speed measured by the meteorological mast anemometers, the measurements of the nacelle wind speed changes systematically in presence of the static yaw error. This aspect has up to now been overlooked in the literature. Therefore, the results of this work might stimulate a critical revision of the existing methods for static yaw error diagnosis and the formulation of new ones.
Keywords: wind energy; wind turbines; measurement; yaw error; anemometer; instrumentation